ANALYSIS OF PROTEIN IN WHEAT GRAIN - Prabha Annavarapu, Venkata Naga Kaumudi; Pamarthi, Murali Krishna (International Journal of Research -GRANTHAALAYAH, 2021)
Wheat is one of the most important cereal crops grown with highest demand. Nitrogen content that enables the protein in the grain is necessary for baking and processing quality. The importance of wheat protein and its functionality in bakery products are well discussed in the given topic. This Study was carried out to study the effect of nitrogen fertilizer supply and its implications on bread wheat variety in the baking process. Dumas method is used for estimating the protein content in the bread variety that is grown in two different nitrogen fertilizers supply with 100kg/ha and 350kg/ha respectively. The results clearly depict the highest growth of bread wheat variety which was grown in 350kg/ha of nitrogen supply has high amount of protein content. Wheat is the best source of carbohydrates and the proteins present in are gliadin and glutenin which are responsible to provide viscoelastic properties in the bakery products. Functionality of the bakery products are well discussed in the introduction part. The result includes test values and graphs have been plotted based on the comparison of protein present in bread. In the discussion section the differences and effects of protein in processing of foods are analysed against similar other research works.